Chicago's Grand Midway : a walk around the world at the Columbian Exposition - Bolotin, Norm, 1951- (University of Illinois Press, 2017)
"The Midway Plaisance at the World's Columbian Exposition of 1893 was designed to complement the vastness of the fair itself, simultaneously entertaining and educating the fairgoer. A half-mile long, the Midway was designed to delight visitors with grandeur, excitement, and surprise. This volume escorts readers through the Midway, showing every feature and intersection, from the Libbey Glass Factory, the Captive Balloon, Little Cairo, and the greatest marvel of all, the Ferris Wheel, capable of carrying 1000 people at a time"